Colapso de la cubierta metálica de un polideportivo; patologías singulares y recurrentes - Alegre, V.; Ródenas, V.; Villalba, S. (Revista ALCONPAT, 2012)
Non common pathologies can be presented occasionally and recurrently as in this case study. This happens especially because of a lack of knowledge transmission. Most damage studies must serve to prepare standards and documents to avoid risk situations. It is presented the collapse of a space frame roof with circular stainless steel bars with joints of stainless steel which threads the extremes of the space frame bars.Key words: local and global buckling; space frame roof; disasters; repeated pathology.